OP0031 Prolonged exposure of t cells to tnf downregulates tcrΖ and expression of the tcr/cd3 complex. (1st June 2001) - Isomäki, P; Yasin, N; Annenkov, A; Clark, J; Foxwell, B; Chernajovsky, Y; Cope, A
Abstract : Background: A role for tumour necrosis factor α (TNF) in the pathogenesis of chronic inflammatory is now firmly established. Paradoxically, TNF also has potent immuno-modulatory effects on CD4 + T lymphocytes, since antigen specific proliferative and cytokine responses are suppressed following prolonged exposure to TNF. We studied whether TNF attenuated T cell activation by uncoupling proximal TCR signal transduction pathways using a mouse T cell hybridoma model. In this model, IL-2 production following peptide stimulation was suppressed by up to 90% by chronic TNF exposure, and was restored to control levels within days of withdrawing TNF signals. Dose-response studies indicated that TNF-treated T cells required TCR engagement with higher peptide concentrations for longer periods of time for commitment to IL-2 production. Subsequent experiments revealed that chronic TNF exposure led to a reversible loss of TCRζ chain expression, in part through a reduction in gene transcription. Downregulation of TCRζ impaired TCR/CD3 assembly and expression at the cell surface, and uncoupled membrane proximal tyrosine phosphorylation events, including phosphorylation of the TCRζ chain itself, CD3ε, ZAP-70 protein tyrosine kinase and LAT. Intracellular Ca 2+ mobilisation was also suppressed in TNF-treated T cells. Signals transduced through a single chain Fv antibody/FcRγ chain chimeric receptor that recognises native type II collagen, and which utilises TCRζ for IL-2 gene transcription, were also attenuated. We propose that TNF may contribute to T cell hyporesponsiveness in chronic inflammatory and infectious diseases, such as rheumatoid arthritis, by mechanisms which include downregulation of TCRζ expression. We speculate that by uncoupling proximal TCR signals TNF could also interrupt mechanisms of peripheral tolerance which are dependent upon intact TCR signal transduction pathways. Objectives: Methods: Results: Conclusion: